Problematika Hukum Kloning Manusia dalam Perspektif Hak Asasi Manusia dan Bioetika - Abd. Rahman Hakim Hasibuan; Daulat Saragi; Yakobus Ndona (Universitas Negeri Medan, 2026)
The development of modern biotechnology has reached a point where human cloning is no longer mere science fiction but rather a technical possibility. However, this progress leaves a significant gap in legal norms. This study aims to analyze the legal status of human cloning practices and its implications for the concepts of legal subjects and human rights. Using normative juridical research methods, this article examines international and national legal instruments. The analysis shows that the majority of current legal frameworks prohibit reproductive cloning as a violation of human dignity, but ambiguity remains regarding therapeutic cloning. Adaptive regulatory reconstruction is needed to prevent the future commodification of humans.